Detection of Sutterella spp. in Broiler Liver and Breast - Derqaoui, Sophia; Oukessou, Mohammed; Attrassi, Kawtar; Elftouhy, Fatima Zahra; Nassik, Saadia (Frontiers in Veterinary Science, 2022)
Sutterella sp. is a gram-negative, microaerophilic bacterium that is particularly resistant to bile acids. It has recently been associated with several human pathologies such as inflammatory bowel disease, asthma, diabetes, and autism. Indeed, susceptibility patterns to ciprofloxacin and erythromycin, combined with resistance to metronidazole, indicate that Sutterella wadsworthensis patterns are closer to those of Campylobacter. The objective of this study is to identify, for the first time, Sutterella spp. in the liver and breast of broiler chickens by quantitative real-time PCR (qPCR). Liver, breast, and cecal content samples were taken from 25 birds and frozen at −20°C until analyzed. The main results showed that Sutterella sp. is part of the cecal microbiota of 48% of the birds and present in the liver and breast of, respectively 20 and 40% of the chicks with a variable Cq. We, therefore, conclude that Sutterella sp. exists in poultry and poultry meat and that foodstuffs of poultry origin might be considered as a potential source of contamination for humans.